1998
DOI: 10.1007/s004320050189
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein thrombosis in hepatocellular carcinoma: age and sex distribution in an autopsy study

Abstract: The purpose of this work was to investigate the prevalence, associated features and effect on survival of portal vein thrombosis (PVT) complicating hepatocellular carcinoma (HCC). The autopsy data of a series of 72 consecutive patients (57 male, 15 female) with HCC were reviewed. PVT was found in 32/72 patients (44%), and tended to be more common in female patients (10/15 versus 22/57, P = 0.052). Stratifying the data according to gender, it appeared that the mean age of patients with PVT compared to those wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
108
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(114 citation statements)
references
References 20 publications
4
108
2
Order By: Relevance
“…Vascular invasion was found in 23.5% in our HCC patients. These results are not congruous with the results of Pirisi et al [17] which showed that the portal vein thrombosis represented 44% in an autopsied HCC specimen. Another study done by Abdel-Wahab et al [18] documented that only 15.9% had portal vein thrombosis.…”
Section: Discussioncontrasting
confidence: 66%
“…Vascular invasion was found in 23.5% in our HCC patients. These results are not congruous with the results of Pirisi et al [17] which showed that the portal vein thrombosis represented 44% in an autopsied HCC specimen. Another study done by Abdel-Wahab et al [18] documented that only 15.9% had portal vein thrombosis.…”
Section: Discussioncontrasting
confidence: 66%
“…(25,(28)(29)(30)(31)(32) However, little is known about factors predictive for PVT in patients with HCC. In a single autopsy study of 72 patients with HCC PVT was found in 44%, and female sex and older age were identified as predictive factors (26).…”
mentioning
confidence: 98%
“…Like most cancers, HCC is also associated with hemostatic activation, with a reported incidence of PVT ranging from 20%-65% (24)(25)(26)(27). As with other cancer-associated thromboses, the presence of PVT in patients with HCC is associated with reduced survival.…”
mentioning
confidence: 99%
“…It has high morbidity even in small-cell hepatic carcinoma. 1 Chau studied 37 resected specimens whose diameters were less than 2 cm, and 40.5% of these specimens showed vein tumor embolisms under light microscopy. 2 At the same time, the prognosis of hepatic carcinoma with PVTT is very poor.…”
Section: Discussionmentioning
confidence: 99%
“…1 The prevalence of PVTT is very high even in small-cell hepatocellular carcinoma (HCC). 2 The prognosis of HCC combined with PVTT is poor.…”
Section: Introductionmentioning
confidence: 99%